Consolidating the Profession? The Professoriate in the 1950s and 1960s - Amy D. Rose; Catherine A. Hansman (Adult Education Research Conference, 2015)
This paper explores the development and growth of an adult education professoriate and adult education programs in higher education from 1945 until 1964. It examines specifically the factors that caused the growth of programs; decisions about curriculum; and the principal sources of funding. Additionally it explores the varying discussions and debates about the nature of the field.
Keywords: history; adult education; professoriate